2013
DOI: 10.7897/2230-8407.04551
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactive Compounds and Antioxidant Properties of Methanolic Extract of Fennel (Foeniculum Vulgare Miller)

Abstract: Methanolic extract of dried Fennel (Foeniculum vulgare Miller) seeds was analyzed for the presence of bioreactive compounds: ascorbate, riboflavin, tocopherol and polyphenols with potential antioxidant properties. The extract had low ascorbate (197.12+1.82µg), riboflavin (11.97+0.35µg) and tocopherol (280.33+5.67µg/g dry seeds) content. However the extract had high polyphenol content (16.506+0.32mg/g dry seeds). Antioxidant activity of the extract was determined by various mechanisms including DPPH free radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 15 publications
3
53
0
1
Order By: Relevance
“…Researchers reported that where they bring about their effect, causing either an increase in ion permeability and leakage of vital intracellular constituents, or impairment of the bacterial enzyme systems (Ratledge and Wilkinson, 1988;Wendakoon and Sakaguchi, 1995). Dua et al (2013) reported that antibacterial activities of Foeniculum vulgare Miller seeds were found as 11 mm inhibition zone against S. aureus (Dua et al, 2013). This report also supports the results we obtained from our study.…”
Section: Discussionsupporting
confidence: 90%
“…Researchers reported that where they bring about their effect, causing either an increase in ion permeability and leakage of vital intracellular constituents, or impairment of the bacterial enzyme systems (Ratledge and Wilkinson, 1988;Wendakoon and Sakaguchi, 1995). Dua et al (2013) reported that antibacterial activities of Foeniculum vulgare Miller seeds were found as 11 mm inhibition zone against S. aureus (Dua et al, 2013). This report also supports the results we obtained from our study.…”
Section: Discussionsupporting
confidence: 90%
“…After incubating at 37°C for 6 h the contents were chilled and 5 ml of 85 % H 2 SO 4 was added slowly. The absorbance was read at 540 nm against reagent blank after 30 minutes 10 . A calibration curve of ascorbic acid (1-20 µg/ml) was prepared.…”
Section: Antioxidant Analysismentioning
confidence: 99%
“…Within 2 minutes, 3 ml of H 2 O 2 -water solution (1:1) was added and pH adjusted to 7.0 with NaOH. The fluorescence by the filtrate was measured at 530 nm with excitation at 470 nm using fluorescence spectrophotometer 10 . Standard riboflavin (1 µg/ml) was used for calibration purpose.…”
Section: Antioxidant Analysismentioning
confidence: 99%
“…Traditionally, fennel seeds are used as anti-inflammatory, analgesic, carminative, diuretic and antispasmodic agents. Recently there has been considerable interest in the antioxidant potential and antimicrobial activities of fennel seed extracts and essential oil [2][3] . Cardamom, is one of the most widely known spices due to its strong aroma and flavor.…”
Section: Mean Salivary Ph Scoresmentioning
confidence: 99%